Nuclear factor κB is a molecular target for sulforaphane-mediated anti-inflammatory mechanisms - Heiß, Elke; Herhaus, Christian; Klimo, Karin; Bartsch, Helmut; Gerhäuser, Clarissa (The journal of biological chemistry, 2001)
Sulforaphane (SFN), an aliphatic isothiocyanate, is a known cancer chemopreventive agent. Aiming to investigate anti-inflammatory mechanisms of SFN, we here report a potent decrease in lipopolysaccharide (LPS)-induced secretion of pro-inflammatory and pro-carcinogenic signaling factors in cultured Raw 264.7 macrophages after SFN treatment, i.e. NO, prostaglandin E2, and tumor necrosis factor α. SFN did not directly interact with NO, nor did it inhibit inducible nitric-oxide synthase enzymatic activity. Western blot analyses revealed time- and dose-dependent reduction of LPS-induced inducible nitric-oxide synthase as well as Cox-2 protein expression, which was suppressed at the transcriptional level. To reveal the target of SFN beyond its anti-inflammatory action, we performed electrophoretic mobility shift assay analyses of transcription factor-DNA binding. Consequently, nuclear factor κB (NF-κB), a pivotal transcription factor in LPS-stimulated pro-inflammatory response, was identified as the key mediator. SFN selectively reduced DNA binding of NF-κB without interfering with LPS-induced degradation of the inhibitor of NF-κB nor with nuclear translocation of NF-κB. Because SFN can interact with thiol groups by dithiocarbamate formation, it may impair the redox-sensitive DNA binding and transactivation of NF-κB. Sulforaphane could either directly inactivate NF-κB subunits by binding to essential Cys residues or interact with glutathione or other redox regulators like thioredoxin and Ref-1 relevant for NF-κB function. Our data provide novel evidence that anti-inflammatory mechanisms contribute to sulforaphane-mediated cancer chemoprevention.